The Gaia-ESO Survey: Stellar content and elemental abundances in the massive cluster NGC 6705 - Cantat-Gaudin, T.; Vallenari, A.; Zaggia, S.; Bragaglia, A.; Sordo, R.; Drew, J. E.; Eisloeffel, J.; Farnhill, H. J.; Gonzalez-Solares, E.; Greimel, R.; Irwin, M. J.; Kupcu-Yoldas, A.; et al. (2014)
Context. Chemically inhomogeneous populations are observed in most globular clusters, but not in open clusters. Cluster mass seems to play a key role in the existence of multiple populations. Aims: Studying the chemical homogeneity of the most massive open clusters is needed to better understand the mechanism of their formation and determine the mass limit under which clusters cannot host multiple populations. Here we studied NGC 6705, which is a young and massive open cluster located towards the inner region of the Milky Way. This cluster is located inside the solar circle. This makes it an important tracer of the inner disk abundance gradient. Methods: This study makes use of BVI and ri photometry and comparisons with theoretical isochrones to derive the age of NGC 6705. We study the density profile of the cluster and the mass function to infer the cluster mass. Based on abundances of the chemical elements distributed in the first internal data release of the Gaia-ESO Survey, we study elemental ratios and the chemical homogeneity of the red clump stars. Radial velocities enable us to study the rotation and internal kinematics of the cluster. Results: The estimated ages range from 250 to 316 Myr, depending on the adopted stellar model. Luminosity profiles and mass functions show strong signs of mass segregation. We derive the mass of the cluster from its luminosity function and from the kinematics, finding values between 3700 M⊙ and 11 000 M⊙. After selecting the cluster members from their radial velocities, we obtain a metallicity of [Fe/H] = 0.10 ± 0.06 based on 21 candidate members. Moreover, NGC 6705 shows no sign of the typical correlations or anti-correlations between Al, Mg, Si, and Na, which are expected in multiple populations. This is consistent with our cluster mass estimate, which is lower than the required mass limit proposed in the literature to develop multiple populations. Based on the data obtained at ESO telescopes under programme 188.B-3002 (the public Gaia-ESO spectroscopic survey, PIs Gilmore and Randich) and on the archive data of the programme 083.D-0671.Full Table 2 is only available at the CDS via anonymous ftp to http://cdsarc.u-strasbg.fr (ftp://130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/569/A17
Keywords: Astrophysics - Solar and Stellar Astrophysics; open clusters and associations: general; open clusters and associations: individual: NGC 6705; stars: abundances